2008
DOI: 10.1007/s11845-008-0122-6
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endovascular abdominal aortic aneurysm repair leads to a reduction in wound complications

Abstract: Percutaneous EVAR is both a feasible and safe method of performing endovascular abdominal aortic aneurysm repair, which is associated with a reduction in wound complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…However, our study demonstrates that performing a concomitant procedure is a predictor of percutaneous access failure. A significantly decreased mean total operative time 28 and a shorter length of hospital stay 3, 6, 9, 10 were noted in many previous studies in pEVAR patients when compared to cEVAR patients. Prior studies have noted wound complications ranging from 0–11% 9, 14 with a rate of 5.0% 2 noted in the randomized trial.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…However, our study demonstrates that performing a concomitant procedure is a predictor of percutaneous access failure. A significantly decreased mean total operative time 28 and a shorter length of hospital stay 3, 6, 9, 10 were noted in many previous studies in pEVAR patients when compared to cEVAR patients. Prior studies have noted wound complications ranging from 0–11% 9, 14 with a rate of 5.0% 2 noted in the randomized trial.…”
Section: Discussionmentioning
confidence: 52%
“…2 Several small single center studies using a variety of grafts showed a reduction in total operative time 28 and length of hospital stay. 3, 6, 9, 10 Additionally, access-related complication rates were lower with pEVAR compared to cEVAR. 2, 4, 612 Despite these promising results, the possibility of publication bias should be considered.…”
Section: Introductionmentioning
confidence: 92%
“…Previously published studies have reported success rates varying from 71% to 100% for percutaneous closure after endovascular aneurysm repair. [2,3,5,1419] Our 95% technical success rate was at the high end of this range. Previous studies noted various factors associated with percutaneous closure failure, including a small-diameter access vessel, certain types of closure devices, femoral artery calcification, access vessel tortuosity, and groin scars.…”
Section: Discussionmentioning
confidence: 78%
“…6 However, impact on LOS has been modest, with a mean of 3.5 days in open access compared to 2.7 days in those who had PEVAR in studies comparing both approaches. [7][8][9] The overall cost of EVAR has been reported to be higher than open repair mainly due to device costs, surveillance imaging and reinterventions 10,11 ; however, the cost analysis of the Open vs Endovascular Repair (OVER) trial reported that in-hospital costs were lower with EVAR persisting up to 2 years. 12 Since device costs are somewhat fixed, decreasing intensive care and overall hospital LOS and wound complications would further decrease the cost of EVAR.…”
mentioning
confidence: 99%